Proprotein Convertase Subtilisin/Kexin Type 9, Brain Cholesterol Homeostasis and Potential Implication for Alzheimer’s Disease - Adorni, Maria Pia; Ruscica, Massimiliano; Ferri, Nicola; Bernini, Franco; Zimetti, Francesca (Frontiers in Aging Neuroscience, 2019)
Alzheimer's disease (AD) has been associated with dysregulation of brain cholesterol homeostasis. Proprotein convertase subtilisin/kexin type 9 (PCSK9), beyond the known role in the regulation of plasma low-density lipoprotein cholesterol, was firstly identified in the brain with a potential involvement on brain development and apoptosis. However, its role in the central nervous system and in AD pathogenesis is still far from being understood. While in vitro and in vivo evidence led to controversial results, genetic studies did not apparently find an association between PCSK9 loss of function mutations and AD risk or prevalence. In addition, a potential impairment of cognitive performances by the treatment with the PCSK9 inhibitors alirocumab and evolocumab, have been excluded, although ongoing studies with longer follow-up will provide further insights. PCSK9 is able to affect the expression of neuronal receptors involved in cholesterol homeostasis and neuroinflammation and higher PCSK9 concentrations have been found in the cerebrospinal fluid of AD patients. In this review, we critically examined the science of PCSK9 with respect to its modulatory role of the mechanisms underlying the pathogenesis of AD. In addition, based on literature data, we made the hypothesis to consider brain PCSK9 as a negative modulator of brain cholesterol homeostasis and neuroinflammation and a potential pharmacological target for treatment.